Pengaruh pengembangan karir dan motivasi terhadap kinerja pegawai negeri sipil di badan penelitian, pengembangan, dan perencanaan Kabupaten Polewali Mandar - Nadia, Sahnaz; Pratminingsih, SA. (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of career development and motivation on the performance of civil servants in the Agency for Research, Development and Planning Kab. Polewali Mandar. The research was conducted using quantitative methods with descriptive and verification methods, namely collecting, presenting, analyzing and testing hypotheses, and making conclusions and suggestions. The dependent variable in this study is Civil Servant Performance (Y) and the independent variable is Career Development (X1) and Motivation (X2). The population and sample of the study were 67 Civil Servants at the Research, Development and Planning Agency of the Regency. Polewali Mandar. Based on the results of the study, it can be concluded that: (1) Career Development has a positive and significant effect on the performance of Civil Servants; (2) Motivation has a positive and significant effect on the performance of Civil Servants; (3) Simultaneously (overall) career development and motivation have a positive and significant effect on the performance of Civil Servants.